2011
DOI: 10.1063/1.3595742
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the night heat losses of hot water storage tanks in thermosyphon solar water heaters

Abstract: The effects of night heat losses on the performance of thermosyphon solar water heaters have been experimentally examined. Three typical thermosyphon solar water heating systems with different storage tank sizes were tested by utilising the method suggested by ISO 9459-2:95. The results were analysed to quantify the night heat losses and to investigate the effect that these may have on the system daily performance. Analysis of the results showed that a linear behavior of the heat losses with the night mean amb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Afterwards and due to the poor isolation on the thermotank, the efficiency starts to drop rapidly and even some negative values are reported. The losses recorded during the night were on the order of 10°C when on a commercial tank might be way smaller [12,13]. Additionally, no insulation was used on the collector during this test.…”
Section: Performance Test With 202 Littersmentioning
confidence: 99%
“…Afterwards and due to the poor isolation on the thermotank, the efficiency starts to drop rapidly and even some negative values are reported. The losses recorded during the night were on the order of 10°C when on a commercial tank might be way smaller [12,13]. Additionally, no insulation was used on the collector during this test.…”
Section: Performance Test With 202 Littersmentioning
confidence: 99%
“…They further reported that the reduction in performance is outweighed by the benefit of freeze protection provided by incorporating a collector loop heat exchanger in the system. Michaelides et al 7 reported that under no load conditions, the night energy losses represent the maximum heat losses in the storage tanks of thermosyphon solar water heaters. They further concluded that average night losses in the storage tank of thermosyphon solar water heaters amount to the single most important energy loss of the solar collector system amounting to an average of 40% of the collected energy.…”
mentioning
confidence: 99%
“…Studies on the performance of thermosyphon solar water heating systems have been conducted by several researchers such as Morrison, 5 Morrison et al, 6 and Michaelides et al 5,7 (solar collector often acts as a thermal emitter at night resulting in a reverse circulation of water from the top of the storage tank to the collectors due to lower air temperature at night during a 24 h period). As such, a percentage of the energy collected during the day is lost.…”
mentioning
confidence: 99%
“…The thermal behavior of the systems involves a lot of interrelated parameters, such as solar radiation and weather conditions, the water flow rate through the collector, the tank configuration (vertical or horizontal), the effectiveness of the heat exchanger (for an indirect heating system) and the thermal load. The night heat loss (or thermosyphonic reverse flow) is another major concern [19]. In addition, to enhance the thermal efficiency, it is critical to prompt and maintain temperature stratification in the tank.…”
Section: Introductionmentioning
confidence: 99%